Insights into lncRNAs in Alzheimer's disease mechanisms. Issue 7 (3rd July 2021) - Li, Dingfeng; Zhang, Juan; Li, Xiaohui; Chen, Yuhua; Yu, Feng; Liu, Qiang
ABSTRACT: Alzheimer's disease (AD) is a progressive neurodegenerative disorder and the most common dementia among the elderly. The pathophysiology of AD is characterized by two hallmarks: amyloid plaques, produced by amyloid β (Aβ) aggregation, and neurofibrillary tangle (NFT), produced by accumulation of phosphorylated tau. The regulatory roles of non-coding RNAs (ncRNAs), particularly long noncoding RNAs (lncRNAs), have been widely recognized in gene expression at the transcriptional and posttranscriptional levels. Mounting evidence shows that lncRNAs are aberrantly expressed in AD progression. Here, we review the lncRNAs that implicated in the regulation of Aβ peptide, tau, inflammation, cell death, and other aspects which are the main mechanisms of AD pathology. We also discuss the possible clinical or therapeutic utility of lncRNA detection or targeting to help diagnose or possibly combat AD.